2018
DOI: 10.1097/md.0000000000010689
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters and treatment time delay in Korean patients with ST-elevation myocardial infarction on admission

Abstract: Most patients with acute myocardial infarction (AMI) experience more than one symptom at onset. Although symptoms are an important early indicator, patients and physicians may have difficulty interpreting symptoms and detecting AMI at an early stage. This study aimed to identify symptom clusters among Korean patients with ST-elevation myocardial infarction (STEMI), to examine the relationship between symptom clusters and patient-related variables, and to investigate the influence of symptom clusters on treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The fact that the classic ACS symptom cluster in combination with other symptom clusters was associated with a higher adjusted odds of using EMS supports the hypothesis that it takes more than "just angina" to cross the threshold to be "serious enough" to get patients with a history of ACS to seek care as compared with those without preexisting angina. [38][39][40] These findings suggest that it takes more than correct symptom attribution of having symptoms with a cardiac etiology to necessitate EMS use. Although correct symptom interpretation in patients experiencing their first ACS event has been shown to be associated with higher odds of using EMS, 5 this is not always the case for patients with recurrent events.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The fact that the classic ACS symptom cluster in combination with other symptom clusters was associated with a higher adjusted odds of using EMS supports the hypothesis that it takes more than "just angina" to cross the threshold to be "serious enough" to get patients with a history of ACS to seek care as compared with those without preexisting angina. [38][39][40] These findings suggest that it takes more than correct symptom attribution of having symptoms with a cardiac etiology to necessitate EMS use. Although correct symptom interpretation in patients experiencing their first ACS event has been shown to be associated with higher odds of using EMS, 5 this is not always the case for patients with recurrent events.…”
Section: Discussionmentioning
confidence: 98%
“…Investigators from prior studies have hypothesized that some patients with a history of ACS "wait and see" to avoid "going too quickly" labeling symptoms as their "typical angina" with the expectations that symptoms will resolve with rest or NTG. 24,26,39 Even if symptoms do not resolve in a timely manner, they may still select another mode of transportation to the hospital, based on appraising the situation as a lower level of illness threat 28 because of event familiarity. 12,24 Alternatively, other patients with a history of angina may promptly recognize and interpret symptoms accurately, yet falsely believe private transportation gets them to the hospital faster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of delay varied in these patients according to time. For instance, it has been reported that the majority of STEMI patients (59%) presented within 6 h of symptom onset and only 25% of patients waited > 60 min (22,23). In another study, it has been shown that up to 33% of STEMI patients would wait > 12 h to seek medical care (20).…”
Section: Prevalence Of Delay In Seeking Carementioning
confidence: 99%
“…The symptoms of AMI are varied, and multiple symptoms often coexist, creating a negative symptom cluster synergy between symptoms. Compared with single symptoms, symptom clusters can increase the burden of disease in AMI patients, decrease their adherence to treatment, and have a serious negative impact on their quality of life and health status (15)(16)(17). The results of related studies have shown that symptom clusters in AMI patients can have a serious impact on functional status, readmission rates for cardiovascular events, and all-cause mortality (18).…”
Section: Introductionmentioning
confidence: 99%